A comparison of low-shock and centrifuge calibrations using piezoresistive accelerometers. (24th January 2018) - Nozato, Hideaki; Shimizu, Masao; Nakao, Shinji; Chiba, Sakae; Ota, Akihiro; Kokuyama, Wataru; Hattori, Koichiro
Abstract: This paper describes the degree of equivalence between low-shock and centrifuge calibrations up to 10 000 m s −2 against three types of piezoresistive accelerometer: an undamped sputter gauge type, a damped sputter gauge type and an undamped semiconductive type. The complex sensitivity in the low-shock calibration and the DC sensitivity in the centrifuge calibration are well consistent within each expanded uncertainty in the frequency domain, together with the vibration calibration using the second-order transfer function. In addition, the preliminary uncertainty budget in the centrifuge calibration facility is also indicated, and distinctly estimated from the viewpoint of the mechanical parts and accelerometers.